Pengaruh Kompensasi, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Pos indonesia Kantor Pos Wonogiri - Maharani, Annisa; , Nur Achmad. S.E., M.Si (2016)
The objective of this study is to determine the influence of compensation, motivation and work discipline towards employee performance in PT Pos Indonesia, Wonogiri Post Office. The sampling technique used in this study is purposive sampling. The data type and source of data used in this study is primary data which is collected from the respondents who have filled in the questionnaire. The test instrument used to test the feasibility of the question is validity and reliability tests. The data analysis method used in this study is multiple linear regression tests which reinforced by F test, t test, normality test and multicollinearity test which shows: (1) There is positive and significant compensation influence towards employee performance which is shown by significance value of 0,030 (<0,05). (2) There is positive and significant motivation influence towards employee performance which is shown by significance value of 0,035 (<0,05). (3) There is positive and significant work discipline influence towards employee performance which is shown by significance value of 0,037 (<0,05). (4) There is positive and significant compensation, motivation and discipline towards employee performance simultaneously which is shown by significance value of 0,000 (<0,05). It can be concluded that the employees of PT Pos Indonesia, Wonogiri Post Office need compensation, motivation and work discipline to improve their work performance in order to reach the company's goals and objectives.